Good governance as a strategic approach to reduce corruption in Algeria - Boudjadi, Saliha; Tabi, Nouara (The International tax journal, 2026)
Corruption is one of the most prominent obstacles facing developing countries, including Algeria, where this phenomenon has spread despite legal and institutional reforms. The concept of good governance is presented as a means of increasing transparency, accountability and improving the performance of institutions. This study seeks to analyse the relationship between good governance and the reduction of corruption in Algeria, to highlight the challenges that hinder the achievement of effective results, and to emphasise the importance of adopting comprehensive legal and societal approaches in order to increase citizens’ trust in the state and to combat corruption effectively.